Community Empowerment in the Management of Type 2 Diabetes Mellitus Through Diabetes Self-Management Education in Perbarakan Village - Cahaya Artha Anastasia Gultom; Syah Fara Dilla; Sari Desi Ulina Sitepu; Lia Debora Manihuruk; Juni Mariati Simarmata (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Kesehatan Medistra Lubuk Pakam, 2026)
Background: Long-term management is required for Type 2 Diabetes Mellitus (T2DM), a chronic disease, to prevent complications and improve patients' quality of life. Insufficient knowledge regarding diabetes management may hinder patients from performing effective self-care. One strategy that can be implemented is Diabetes Self-Management Education (DSME), a structured educational approach designed to enhance patients’ knowledge and skills in managing their condition. Methods: This community service activity involved 33 individuals with Type 2 Diabetes Mellitus in Perbarakan Village. The DSME-based educational program covered fundamental concepts of diabetes, dietary management, physical activity, medication adherence, blood glucose monitoring, complication prevention, and diabetes problem-solving. Participants’ knowledge was assessed before and after the educational intervention using pre-test and post-test questionnaires.Results: The majority of participants were male (51.5%), had a junior high school education (36.4%), worked as entrepreneurs (33.3%), had comorbid conditions (60.6%), and had been diagnosed with diabetes for 1–3 years (57.6%). Before the intervention, most participants demonstrated poor (48.5%), moderate (33.3%), and good (18.2%) levels of knowledge. Following the educational intervention, the proportion of participants with good knowledge increased to 51.5%, while those with moderate knowledge accounted for 39.4%, and the proportion with poor knowledge decreased to 9.1%. Conclusion: Diabetes Self-Management Education (DSME) effectively improved participants’ knowledge regarding Type 2 Diabetes Mellitus management. These findings suggest that self-management-based health education can help communities better understand how to manage diabetes independently and prevent diabetes-related complications.